1996
DOI: 10.3354/dao027233
|View full text |Cite
|
Sign up to set email alerts
|

Use of non-lethal procedures to detect and monitor Aeromonas salmonicida in potentially endangered or threatened populations of migrating and post-spawning salmon

Abstract: Non-lethal assay of mucus was assessed for mittently shown to either infect or cause disease in detection of Aeromonas salmon~cida among feral populations of salmon returning to the Salmon River (Altmar NY USA) A salmon~cida was isolated from returns of 2 year classes of coho Oncorhynchus kisutch and chinook 0 tshawytscha salmon Data suggested that non-lethal assay of mucus was comparable to standard lethal procedures used to detect and isolate A salmonicida from ludney tissues Non-lethal procedures were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Microbial characterization and subsequent PCR‐based diagnosis of the bacterial isolate involved in septicaemic disease of carps in the present study suggested the causative agent to be Aeromonas hydrophila , Aeromonas veronii and Aeromonas sobria . Though motile aeromonads compose part of normal intestinal microflora of healthy fish, they also cause diverse pathologic conditions that include dermal ulceration, tail or fin rot, erythrodermatitis, haemorrhagic septicaemia, red sore disease, red rot disease and scale protrusion disease (Cipriano et al., 1996). The gross signs of disease on fish observed in this study such as abdominal distention, focal haemorrhagic necrosis, exopthalmia, dropsy, fin and tail rot, and scale protrusion were similar to those observed earlier (Austin & Austin, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial characterization and subsequent PCR‐based diagnosis of the bacterial isolate involved in septicaemic disease of carps in the present study suggested the causative agent to be Aeromonas hydrophila , Aeromonas veronii and Aeromonas sobria . Though motile aeromonads compose part of normal intestinal microflora of healthy fish, they also cause diverse pathologic conditions that include dermal ulceration, tail or fin rot, erythrodermatitis, haemorrhagic septicaemia, red sore disease, red rot disease and scale protrusion disease (Cipriano et al., 1996). The gross signs of disease on fish observed in this study such as abdominal distention, focal haemorrhagic necrosis, exopthalmia, dropsy, fin and tail rot, and scale protrusion were similar to those observed earlier (Austin & Austin, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, diagnosis of infectious hematopoietic necrosis virus (IHNV) and viral hemorrhagic septicemia virus (VHSV) in rainbow trout ( Oncorhynchus mykiss ) previously required euthanizing fish, but researchers demonstrated the ability to diagnose and track infection status over multiple testing periods using fin clips from the same host [ 5 , 6 ]. Furthermore, surveillance of Aeromonas salmonicida in hatchery stocks of Atlantic salmon ( Salmo salar ) utilized non-lethal mucus swabs for early detection of A. salmonicida leading to proper treatment prior to stocking [ 7 ]. The development of more non-lethal detection methods for regulated fish pathogens may substantially benefit surveillance and management in cultured and wild fish populations.…”
Section: Introductionmentioning
confidence: 99%
“…Once it was recognised only to infect salmonids, but it has also been isolated from non salmonids marine and freshwater fish including turbot (Scophthalmus maximus L.), gilthead seabream (Sparus aurata L.), lamprey (Petromyzon marinus L.) and Atlantic cod (Gadus morhua L.) (Austin and Austin, 2007). A. salmonicida is commonly detected in mature wild salmon entering the rivers in the Atlantic US coast (Cipriano et al, 1996) as well as in the Atlantic Coast of Spain (Ortega et al, 2005), which could be one of the reasons for the decline of wild populations in this area where A. salmonicida is also considered to be a limiting factor in the turbot production.…”
mentioning
confidence: 99%